2020
DOI: 10.1186/s12933-020-01089-2
|View full text |Cite
|
Sign up to set email alerts
|

Issues for the management of people with diabetes and COVID-19 in ICU

Abstract: In the pandemic "Corona Virus Disease 2019" (COVID-19) people with diabetes have a high risk to require ICU admission. The management of diabetes in Intensive Care Unit is always challenging, however, when diabetes is present in COVID-19 the situation seems even more complicated. An optimal glycemic control, avoiding acute hyperglycemia, hypoglycemia and glycemic variability may significantly improve the outcome. In this case, intravenous insulin infusion with continuous glucose monitoring should be the choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 76 publications
0
33
0
1
Order By: Relevance
“…In conclusion, the effect of acute hyperglycemia during COVID-19 is not so much surprising and it should be treated according to the already existing guidelines [16][17][18].…”
mentioning
confidence: 95%
“…In conclusion, the effect of acute hyperglycemia during COVID-19 is not so much surprising and it should be treated according to the already existing guidelines [16][17][18].…”
mentioning
confidence: 95%
“…26 However, the studies available at present indicated that even optimal glycemic control, avoidance of acute hyperglycemia, hypoglycemia, and glycemic variability could cause a significant improvement in the outcomes of the COVID-19 patients with diabetes. 27 In a retrospective study carried out in the USA on 451 patients with COVID-19 and diabetes or hyperglycemia, it appeared that patients with uncontrolled hyperglycemia endured longer hospital stays and experienced higher mortality rate in the hospital compared with those whose blood sugar levels were under control. 28 Another study revealed that uncontrolled diabetes with HbA1c >9% corresponded to an approximately 60% greater risk of pneumonia-related hospitalization in the course of the bacterial infection.…”
mentioning
confidence: 99%
“…Several recommendations have been published on how to manage several specific aspects when COVID-19 is present in people with diabetes [2] , [3] , [4] or on how to manage the diabetes therapy during the pandemic [4] , [5] . However, it is clear that any recommendation to be followed needs an interaction between the person with diabetes and the health care professionals, which has been the major challenge in the period of lockdown and social distance [6] .…”
mentioning
confidence: 99%